2005
DOI: 10.1073/pnas.0506657102
|View full text |Cite
|
Sign up to set email alerts
|

Observation and manipulation of subsurface hydride in Pd{111} and its effect on surface chemical, physical, and electronic properties

Abstract: We report the observation and manipulation of hydrogen atoms beneath the surface of a Pd{111} crystal by using low-temperature scanning tunneling microscopy. These subsurface hydride sites have been postulated to have critical roles in hydrogen storage, metal embrittlement, fuel cells, and catalytic reactions, but they have been neither observed directly nor selectively populated previously. We demonstrate that the subsurface region of Pd can be populated with hydrogen atoms from the bulk by applying voltage p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 33 publications
3
63
0
2
Order By: Relevance
“…4(b)). It is found that, for the system at hand, the function is slightly asymmetric with respect to the potential bias sign, which is consistent with the experimental observations by Sykes and co-workers 14 from which the transfer rates are inferred. For more information on the rate model, the reader is referred to the relevant literature.…”
Section: Equations Of Motionsupporting
confidence: 80%
See 2 more Smart Citations
“…4(b)). It is found that, for the system at hand, the function is slightly asymmetric with respect to the potential bias sign, which is consistent with the experimental observations by Sykes and co-workers 14 from which the transfer rates are inferred. For more information on the rate model, the reader is referred to the relevant literature.…”
Section: Equations Of Motionsupporting
confidence: 80%
“…14 The protuberances are most likely due to the clustering of hydrogens in the vicinity of the surface, with the topological feature mostly due to a hydrogen layer at the surface and to the partial population of the subsurface sites. This type of structures has also been inferred from experimental observations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond the possible hydrogen storage applications of such systems, subsurface and bulk hydrogen has been identified as a reaction intermediate for several catalytic reactions on monometallic catalysts, such as alkene hydrogenation on Pd [30,31] and alkene hydrogenation and methanation on Ni [32][33][34][35]. Additionally, subsurface hydrogen has been shown to affect the binding of other species on single crystals and nanoparticles [36]. Thus, a systematic understanding of the stability of subsurface hydrogen and its effect on the reactivity of NSAs would be helpful in establishing a better understanding of their catalytic behavior for hydrogen-related applications and in identifying alloys with promising catalytic properties.…”
Section: Introductionmentioning
confidence: 98%
“…Control at this scale was limited to surfaces until manipulation of individual dopants was first demonstrated in Pd when an STM tip was used to vertically transport H from bulk to subsurface sites by elevating the tip voltage [13].…”
Section: Introductionmentioning
confidence: 99%